ANALISIS FUNDAMENTAL,GROWTH DAN RETURN SAHAM (STUDI EMPIRIS PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2018) - Susilowati, Yeye; Nisa, Kamilatun; Poerwanti, Tjahjaning (Proceeding SENDI_U, 2020)
In this study aims to fundamental analyze, growth and the stock returns of food and beverage companiesfrom the Indonesia Stock Exchange in 2015-2018. The sampling technique used was purposive sampling, with 80companies. The test used for analysis is the multiple linear regression analysis test and the hypothesis used tstatistic calculation at the 5% significance level. The results of his research show that liquidity has a positive andsignificant effect on stock returns, while leverage, activity, profitability and growth indicate that there is no directinfluence on stock returns.